The Avian XPR1 Gammaretrovirus Receptor Is under Positive Selection and Is Disabled in Bird Species in Contact with Virus-Infected Wild Mice - Martin, Carrie (American Society for Microbiology, 2013)
Xenotropic mouse leukemia viruses (X-MLVs) are broadly infectious for mammals except most of the classical strains of laboratory mice. These gammaretroviruses rely on the XPR1 receptor for entry, and the unique resistance of laboratory mice is due to two mutations in different putative XPR1 extracellular loops. Cells from avian species differ in susceptibility to X-MLVs, and 2 replacement mutations in the virus-resistant chicken XPR1 (K496Q and Q579E) distinguish it from the more permissive duck and quail receptors. These substitutions align with the two mutations that disable the laboratory mouse XPR1. Mutagenesis of the chicken and duck genes confirms that residues at both sites are critical for virus entry. Among 32 avian species, the 2 disabling XPR1 mutations are found together only in the chicken, an omnivorous, ground-dwelling fowl that was domesticated in India and/or Southeast Asia, which is also where X-MLV-infected house mice evolved. The receptor-disabling mutations are also present separately in 5 additional fowl and raptor species, all of which are native to areas of Asia populated by the virus-infected subspecies Mus musculus castaneus. Phylogenetic analysis showed that the avian XPR1 gene is under positive selection at sites implicated in receptor function, suggesting a defensive role for XPR1 in the avian lineage. Contact between bird species and virus-infected mice may thus have favored selection of mouse virus-resistant receptor orthologs in the birds, and our data suggest that similar receptor-disabling mutations were fixed in mammalian and avian species exposed to similar virus challenges.